Measurement of income inequality re-examined: constructing experimental tests by questionnaire (Economic and Political Thought, 2016)
Learning ordinary people’s perception of income inequality is a relativelynew field of research, but its importance is rapidly growing. Despite the popularityof inequality measures, the underlying assumptions concerning the mostpopular of them do not fully hold, as shown in early research by Amiel andCowell (1992; 1999). However, results of their study contain multiple puzzlingand inconsistent answers. This paper analyses methods used by Amieland Cowell to elicit respondents’ views about income inequality. It presentsthe results of a quantitative questionnaire repeated after Amiel and Cowell,combined with qualitative interviews with selected respondents. The researchwas conducted in Poland on 132 sociology and economy students. Qualitativeinterviews and the subsequent data analysis revealed multiple problemsthat caused respondents to answer inconsistently. Solutions to some of theseproblems are then proposed.